PENGARUH BELANJA MODAL DAN ALOKASI DANA DESA TERHADAP KEMANDIRIAN DAN KINERJA KEUANGAN DESA DI KABUPATEN JEMBER - Yulihantini, Dinna Tri; Sukarno, Hari; Wardayati, Siti Maria (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2018)
financial performance in Jember Regency. In specific, this study analyzes the influence of capital expenditure and Village Fund Allocation (ADD), as the components of Village Government Budget (APBDes), on village financial performance in terms of its effectiveness and efficiency. This study used secondary data in the form of Realization Reports of APBDes that were collected from the 53 villages for the period of 2015-2016. Data were analyzed using path analysis. Results of the study indicate that capital expenditure and ADD have no influences on the independence of village financial performance, capital expenditure has a negative effect on the effectiveness of village financial performance, while ADD and the independence of village financial performance have no significant effects on the effectiveness of village financial performance. In terms of efficiency, capital expenditure has a negative effect on village financial performance, while ADD has a positive effect on village financial performance. Village financial independence has no effect on the efficiency of village financial performance. Keywords: Capital Expenditure, Village Fund Allocation, Village Financial Independence, Effectiveness and Efficiency of Village Financial Performance.